Virtual Directions in Paleomagnetism: A Global and Rapid Approach to Evaluate the NRM Components - Ramón, Maria J.; Pueyo, Emilio L.; Oliva-Urcia, Belén; Larrasoaña, Juan C. (Frontiers in Earth Science, 2017)
We introduce a method and software to process demagnetization data for a rapid and integrative estimation of characteristic remanent magnetization (ChRM) components. The virtual directions (VIDI) of a paleomagnetic site are “all” possible directions that can be calculated from a given demagnetization routine of “n” steps (being m the number of specimens in the site). If the ChRM can be defined for a site, it will be represented in the VIDI set. Directions can be calculated for successive steps using principal component analysis, both anchored to the origin (resultant virtual directions RVD; m * (n2+n)/2) and not anchored (difference virtual directions DVD; m * (n2-n)/2). The number of directions per specimen (n2) is very large and will enhance all ChRM components with noisy regions where two components were fitted together (mixing their unblocking intervals). In the same way, resultant and difference virtual circles (RVC, DVC) are calculated. Virtual directions and circles are a global and objective approach to unravel different natural remanent magnetization (NRM) components for a paleomagnetic site without any assumption. To better constrain the stable components, some filters can be applied, such as establishing an upper boundary to the MAD, removing samples with anomalous intensities, or stating a minimum number of demagnetization steps (objective filters) or selecting a given unblocking interval (subjective but based on the expertise). On the other hand, the VPD program also allows the application of standard approaches (classic PCA fitting of directions a circles) and other ancillary methods (stacking routine, linearity spectrum analysis) giving an objective, global and robust idea of the demagnetization structure with minimal assumptions. Application of the VIDI method to natural cases (outcrops in the Pyrenees and u-channel data from a Roman dam infill in northern Spain) and their comparison to other approaches (classic end-point, demagnetization circle analysis, stacking routine and linearity spectrum analysis) allows validation of this technique. The VIDI is a global approach and it is especially useful for large data sets and rapid estimation of the NRM components.